Potential effects of environmental toxicants on sperm quality and potential risk for fertility in humans - Sciorio, Romualdo; Greco, Pier Francesco; Greco, Ermanno; Tramontano, Luca; Elshaer, Fathy M.; Fleming, Steven (Frontiers in Endocrinology, 2025)
Semen quality is a key factor in male fertility, but defining normal reference values for semen parameters remain challenging. Over the past four decades, several authors have reported a noticeable decline in sperm parameters, raising concerns about male reproductive health. While the exact causes remain unclear, potential contributors include environmental pollution, endocrine disruptor chemicals (EDCs) and oxidative stress, with the latter becoming a growing concern. Environmental changes and increased exposure to EDCs, such as pesticides, herbicides, bisphenol A (BPA), phthalates, polychlorinated biphenyls (PCBs), and heavy metals, are believed to contribute significantly to the decline in sperm quality. These chemicals impact individuals from prenatal life through adulthood, potentially leading to long-term reproductive consequences. Overall, this review explores the relationship between environmental toxicants, including volatile organic compounds, EDCs, as well as oxidative stress and reduced male fertility. While a substantial body of research has found associations between these exposures and adverse fertility outcomes, some studies have reported no significant associations. The primary objective of this review is to provide a deeper understanding of the potential mechanisms between these environmental chemicals on testicular function and spermatogenesis. It also examines the broader evidence on the decline in sperm quality and explores its potential implications for overall fertility outcomes in humans. By doing so, the review will shed light on the broader public health implications of environmental pollutants and their impact on male reproductive health, emphasizing the need for further research in this critical area.